2009
DOI: 10.1007/s10725-009-9363-2
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of experimental warming and enhanced ultraviolet-B radiation on photosynthesis and antioxidant defense of Picea asperata seedlings

Abstract: Picea asperata is a dominant tree species in the southeast of the Tibetan Plateau of China. This paper studies the short-term effects of warming, enhanced UV-B (290-315 nm) and their combination on growth, photosynthesis and antioxidant defense system (AOS) of P. asperata seedlings. The experimental design included two levels of UV-B (ambient UV-B and enhanced by 30% UV-B) and two levels of temperature (ambient temperature and warmed temperature by 1.74°C). Although enhanced UV-B increased the efficiency of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
49
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 32 publications
5
49
0
1
Order By: Relevance
“…Recent work has confirmed that hydrogen peroxide is a signaling molecule which mediates responses to abiotic stresses in plants; enhanced UV-B increased the efficiency of the antioxidant defense system, including UV-B-absorbing compounds and antioxidant enzyme activity (Han et al, 2009). The H 2 O 2 accumulation we observed in cucumber cotyledons was accompanied by an increase in the activity of antioxidant system enzymes catalyzing reactions of hydrogen peroxide removal: CAT, GPX and SPX.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Recent work has confirmed that hydrogen peroxide is a signaling molecule which mediates responses to abiotic stresses in plants; enhanced UV-B increased the efficiency of the antioxidant defense system, including UV-B-absorbing compounds and antioxidant enzyme activity (Han et al, 2009). The H 2 O 2 accumulation we observed in cucumber cotyledons was accompanied by an increase in the activity of antioxidant system enzymes catalyzing reactions of hydrogen peroxide removal: CAT, GPX and SPX.…”
Section: Discussionsupporting
confidence: 64%
“…Rarely analyzed is the plant response at the seedling stage, especially at a very early stage which is connected with high oxidative activity and the involvement of cotyledons (Jain et al, 2004). There are reports on changes in SOD activity and overproduction of H 2 O 2 as a result of exposure to UV-B radiation in sunflower cotyledons (Yanarelli et al, 2006b) and Picea asperata seedlings (Han et al, 2009). In cucumber cotyledons irradiated with ultraviolet UV-C (254 nm) or UV-A+UV-B (280-360 nm), Watanabe at al.…”
Section: Discussionmentioning
confidence: 98%
“…Substantial efforts are made to study ecological and biological effect of climate warming and nitrogen deposition on plant growth and physiology (Nakaji et al 2001;Pérez et al 2005;Larssen et al 2006;Han et al 2009). It is generally accepted that warming always promotes plant photosynthetic capacity in cold regions (Han et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that warming always promotes plant photosynthetic capacity in cold regions (Han et al 2009). Similarly, nitrogen load usually be helpful for photosynthesis of trees unless the amount of available N in forest soil exceeds the requirement for tree growth (Yao and Liu 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are over 1 million ha dragon spruce plantation in southwestern China, accounting for approximately 50% of the forest area in this region. To date, artificial warming studies in this region have focused more on aboveground components, with less focus on soils and belowground ecosystem processes (Yin et al 2008;Zhang et al 2008;Zhao and Liu 2009;Han et al 2009;Xu et al 2009). …”
mentioning
confidence: 99%